2020
DOI: 10.9734/ajr2p/2020/v3i230115
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Radiation Exposure Level from Some Scrap Metal Dumpsites in Nasarawa State, Nigeria

Abstract: In this study, the radiation exposure rate emanating from the scrap metals dumpsite was assessed using an Interceptor Spectroscopic personal radiation detector (SPRD). Sixteen (16) scrap metal dumpsites were selected at random across four Local Government Areas (Nasarawa, Lafia, Akwanga, and Keffi) of Nasarawa State, Nigeria. The gamma activity level in µrem/hr on three (3) randomly selected points on each of the scrap metal dumpsites was determined. A reading was taken on point 100 m away from each of the scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…All these obtained values were three times lower than the world average value of 57 nGy/hr. This finding was not in accordance with research carried out by Kerinja et al, (2020) and Abah (2014) who found the absorbed dose rate to be above the world average value.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…All these obtained values were three times lower than the world average value of 57 nGy/hr. This finding was not in accordance with research carried out by Kerinja et al, (2020) and Abah (2014) who found the absorbed dose rate to be above the world average value.…”
Section: Resultscontrasting
confidence: 95%
“…Hence, the absorbed dose rate depends on some specific radionuclide concentrations observed during the study. Its well-known that the absorbed dose rate will always be high, If the of radionuclide concentration for the study area is high, (Kerinja et al, 2020). From Table 1.…”
Section: Resultsmentioning
confidence: 99%